Accelerated Aging in Serious Mental Disorders - Bersani, F. Saverio (Curr Opin Psychiatry, 2019)
PURPOSE OF REVIEW: Clinical, epidemiological and biological evidence raise the possibility that serious mental disorders (SMD’s) are associated with accelerated biological aging. To the extent this is true, SMD’s should not simply be considered in terms of mental illness or brain dysfunction, but also as “whole body” and multi-system illnesses, or else as conditions with significant somatic concomitants. RECENT FINDINGS: The concept of accelerated biological aging in SMD’s is supported by reports of accelerated changes in certain biomarkers normally associated with the aging process. SUMMARY: We define and discuss several proposed biological aging markers that have been examined in SMD’s, we review the most recent findings, and we conclude with opinions regarding the merits and meanings of these markers, their usefulness in understanding and treating SMD’s, and remaining questions and future directions in this area of research.